A study on the effectiveness of promotional tools practiced by Parkson Grand Mahkota Parade / Nursyahriah Aini Khirudin - Khirudin, Nursyahriah Aini (Faculty of Business and Management, 2014)
The purpose of this study was to investigate the relationship of the selected independent variables: advertising, sales promotion, direct marketing and personal selling with dependent variable which is the effectiveness of promotional tools. In order to provide a guide in the study, four hypotheses were formulated. Data were collected from 150 respondents using the questionnaire. This study was conducted at Parkson Grand Mahkota Parade. Then the results was analyses by using SPSS to find the significant relationship with the dependent variables. Through this study, it will help Parkson Grand Mahkota Parade to identify the new strategy that can be used to increase their promotions strategy especially to encourage consumers to purchase at Parkson Grand Mahkota Parade.